The Development of Technical English Multimedia Interactive Module to Enhance Student Centered Learning (SCL) - Mohd Shafeirul Zaman, Abd Majid; Mohammad Musab, Azmat Ali; Azwin Arif, Abdul Rahim; Nor Yazi, Khamis (Elsevier, 2012)
Based from the definition found in Longman Dictionary of Contemporary English (Second Impression; 2006), technique can be defined as a special way of doing something whereas technology is referring to new machines, equipment and ways of doing things that are based on modern knowledge about science and computers. Therefore, in teaching and learning processes, technique and technology cannot be apart from each other as both complete the circle of education. In discussing about the usage of technology in delivering the knowledge and information, we can never run from the reality of integrating it into the traditional method, from textbooks and teachers to a more diverse type especially in the learning materials as in recent case, educators are keen on using the latest invention and innovation in their classroom. This is because it will make their tasks easier or they wanted to be in the wave of technologies era or even they believe that such things benefits the students in terms of gaining their understanding in the subject taught. This is the reason why such research is to be conducted in order to make sure that the focus of the teaching and learning processes is now on students whereby the traditional method of using module or book will be replaced by courseware so that it can be more attractive in the sense of students’ acceptance. Besides that, by producing our own courseware, it is hoped that we have answered the call of preserving our nature by using material that is not made from tree and such apart from entering the new phase of integrating technologies in teaching and learning.